Memory B cell response to a PCV-13 booster in 3.5 year old children primed with either PCV-7 or PCV-13. Issue 20 (9th May 2017) - Trück, Johannes; Thompson, Amber; Morales-Aza, Begonia; Clutterbuck, Elizabeth A.; Voysey, Merryn; Clarke, Ed; Snape, Matthew D.; Kelly, Dominic F.; Finn, Adam; Pollard, Andrew J.
Highlights: B cell stimulation is crucial for an effective post-vaccination antibody response. We assessed memory B cell responses to pneumococcal booster vaccination in preschool children. There were large differences between the B cell responses to individual serotypes. Priming and boosting with the same vaccine did not increase memory B cell responses. There was a unique immunological response to serotype 3. Abstract: Pneumococcal protein-polysaccharide conjugate vaccines provide direct protection against Streptococcus pneumoniae through the induction of persistent anti-polysaccharide antibodies, and by priming for a rapid secondary antibody response. Memory B cells (BMEM ) generated during an initial immune response are responsible for both the more rapid and quantitatively greater secondary antibody response and are also thought to contribute to the ongoing production of plasma cells providing long-term antibody persistence. We recruited 3.5-year-old children who had participated in a previous clinical trial comparing infant immunization with either a 7-valent (PCV-7) or a 13-valent pneumococcal conjugate vaccine (PCV-13) to investigate whether prior priming with pneumococcal antigens influences BMEM responses. Blood was taken before and 1 month after a PCV-13 booster. BMEM were quantified using a cultured ELISpot assay for pneumococcal serotypes 1, 3, 4, 14, 19A, 23F, and with diphtheria and tetanus toxoid as controls, and then correlated with serotype-specific IgG concentrations and opsonophagocytic activity (OPA) titers. In total, blood samples from 62 participants were available for analysis. Serotype-specific BMEM frequencies were generally low at baseline (before boost) although for serotypes 14 and 3, they were significantly higher in children primed with PCV-13 than PCV-7 primed children. Following the PCV-13 booster, BMEM frequencies increased and were not different between the groups for all serotypes. A strong inverse correlation was found between antibody concentrations and OPA titers at baseline and BMEM following booster vaccination for serotype 3 but not for other serotypes suggesting that, for this serotype, pre-existing serotype-specific antibodies may inhibit BMEM formation in response to vaccination. Clinicaltrials.gov registration number: NCT01095471.